Comparison of linear measurements of optic cup-to-disk ratio obtained with RTVue OCT and digital retinography - Valdenir Ribeiro Jr. (Arquivos Brasileiros de Oftalmologia)
ABSTRACT Purpose: To compare the linear measurements of the optic disk cup obtained using RTVue optical coherence tomography (OCT) with those obtained using digital retinography. Methods: This is a cross-sectional study performed with digital retinography and RTVue OCT images from patients with glaucoma or patients suspected of glaucoma. In color retinography, the greatest horizontal and vertical diameters of the optic disk starting from the inner edge of the Elschnig ring were obtained using a pachymeter with a grade of 0.01 mm. In OCT, the delineation of the optic nerve was obtained automatically from the horizontal and vertical cup results. Results: One hundred eyes from 100 subjects with a mean age of 60.1 ± 15.7 years were included. Of these, 79 were the right eye and 21 the left eye, with 61 men and 39 women. The mean horizontal cup obtained with OCT was 0.91 ± 0.10, while that obtained with retinography was 0.79 ± 0.11 (p<0.01). Conclusions: There was poor agreement between the evaluated methods in the measurements of optic disk cup excavations. Measurements obtained automatically with OCT RTVue were higher but were significantly correlated with measurements obtained manually with digital retinography. Poor agreement of the optic disk parameters between the two imaging devices was noted.